Extremism drives out moderation - Bettina Klose; Dan Kovenock (Center for Economic Studies and ifo Institute (CESifo), 2012)
This article investigates the impact of the distribution of preferences on equilibrium behavior in conflicts that are modeled as all-pay auctions with identity-dependent externalities. In this context, we define centrists and radicals using a willingness-to-pay criterion that admits preferences more general than a simple ordering on the line. Through a series of examples, we show that substituting the auction contest success function for the lottery contest success function in a conflict may alter the relative expenditures of centrists and radicals in equilibrium. Extremism, characterized by a higher per capita expenditure by radicals than centrists, may persist and lead to a higher aggregate expenditure by radicals, even when they are relatively small in number. Moreover, we show that centrists may in the aggregate expend zero, even if they vastly outnumber radicals. Our results demonstrate the importance of the choice of the institutions of conflict, as modeled by the contest success function, in determining the role of extremism and moderation in economic, political, and social environments.
Keywords: D72; D74; C72; D44; 330; conflict; all-pay auction; identity-dependent externalities; radicalism; extremism; contest success function